Cranial Remodeling Orthosis for Infantile Plagiocephaly Created Through a 3D Scan, Topological Optimization, and 3D Printing Process. - Geoffroy, Maya; Gardan, Julien; Goodnough, Jason; Mattie, Johanne (Journal of Prosthetics & Orthotics (JPO), 2018)
Purpose: This article presents a novel design of a cranial remodeling orthosis (CRO) helmet developed through a three-dimensional (3D) scanning and 3D printing process to correct an infantile plagiocephaly. Materials and Methods: This research merges a handheld scanner, computer-aided engineering (CAE), and fused deposition modeling (FDM) technologies to propose an alternative to traditional plaster casting. The study finds out all criteria that will merge with requirements, 3D scanning, topological optimization into the CAE, and 3D printing to implement the design for manufacturing (DFM) approach to get a reproducible process that is less invasive for the child. Results: The project identifies the current limitations and creates design requirements and acceptance criteria to define a design and manufacturing process using a topological optimization method. Based on a child's skull 3D scan, the application aims to manufacture a CRO helmet due to clinical criteria by 3D printing. The new design aims to reduce the time from assessment to initial fitting and to reduce the temperature within the CRO. The project has manufactured a CRO helmet by fused depositing modeling in 3D printing to characterize its mechanical behavior and analyze the possible improvements. Conclusions: Limitations were found in the material used in the 3D printing, and some recommendations are made to improve the method. The DFM approach is useful for improving the final product by considering manufacturing and use constraints as soon as possible in the design stage, such as part orientation, infill density, and topological optimization parameters as well as the practitioner' skills. The main novelty is to have developed a 3D scanning and 3D printing process to correct an infantile plagiocephaly to obtain a CRO helmet responding to use and manufacturing constraints while proposing a suitable organic shape.